Mapping of pH, EC, and TDS Parameters to Identify Water Quality in Situ Cisanti - Hanifah, Shofie Dzakia; Hendrayani, Riska; Carrisa, Refi; Rizki, Muhammad Ilham; Rohman, Muhammad Alkuansinta; Hutabalian, May Angelia; Rahman, Jafar Shidqur; Sihombing, Feronika Roulitua; Ramadhan, Fadhel; Ramadan, Ananda Zikri; Nugraha, Andhika; Kirana, Kartika Hajar; Fitriani, Dini (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
Situ Cisanti located at Tarumajaya Village, Kertasari District, Bandung Regency, West Java. Situ Cisanti has significant role in supporting the lives of the surrounding community, especially as the central source of clean water. This research was conduct to identify the water quality of Situ Cisanti by mapping the parameters of pH, Electrical Conductivity (EC), and Total Dissolved Solids (TDS). Measurement was take using Combometer Hanna Grocheck HI 9813-6 at 69 points spread over the research area. The result of pH measurement in Situ Cisanti has a range value from 7,7 to 9,7 with an average value of 9. The EC measurement range value is 0,1 mS/cm to 0,9 mS/cm with an average value of 0,13 mS/cm. The TDS measurement range value is 83 mg/L to 141 mg/L, while the average is 100,78 mg/L. Most of the pH values in the study area meet the quality standards for hygiene sanitation water, while the EC and TDS values are below the threshold value, considering it safe for health.